2013
DOI: 10.2139/ssrn.2278911
|View full text |Cite
|
Sign up to set email alerts
|

Job Insecurity and Financial Distress

Abstract: This paper investigates the effects of different job categories on households' likelihood of experiencing financial distress. Given imperfect financial markets and the absence of unemployment subsidies, households with less secure jobs are likely to experience drops in income more frequently than households with well-protected jobs. Households' abilities to deal with financial decisions (i.e. financial literacy) can mitigate these problems. Our results suggest that greater job insecurity increases the probabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The structural equation modeling results indicated that job insecurity negatively and significantly influenced employees' personal FWB whereas work satisfaction was affected by employees' personal FWB directly and indirectly via employees' family FWB. The results supported the general notion that job insecurity leads to financial stress/distress (Barazzetta et al, 2015;Giannetti et al, 2014;Rajani et al, 2016). They also supported Kim et al's (2006) remarks that financial stress affects employees' work satisfaction.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The structural equation modeling results indicated that job insecurity negatively and significantly influenced employees' personal FWB whereas work satisfaction was affected by employees' personal FWB directly and indirectly via employees' family FWB. The results supported the general notion that job insecurity leads to financial stress/distress (Barazzetta et al, 2015;Giannetti et al, 2014;Rajani et al, 2016). They also supported Kim et al's (2006) remarks that financial stress affects employees' work satisfaction.…”
Section: Discussionsupporting
confidence: 84%
“…Inevitably, many people have a strong feeling of job insecurity (Shoss, 2017). Based on responses from more than 7,700 households and 19,000 family members in Italy, Giannetti et al (2014) reported that job insecurity could lead to financial distress (or stress), which was more pronounced for those people who were employed on a parttime basis. The relationship between job insecurity and financial stress was found to be partially mediated by FWB (Choi et al, 2020).…”
Section: Job Insecurity and Employees' Fwbmentioning
confidence: 99%
“…Financial threat is an emotional state which refers to “self-reported fearful-anxious uncertainty regarding one’s current and future financial situation” [35, p. 129; see also [7]. Financial threat perception, or financial distress, is usually associated with people or households that experience job insecurity when their jobs are less secure and have low protection against unemployment [36], and the data confirm that the financial threat is higher for people who experience a large number of economic difficulties in their daily life [37]. Economic difficulties can also become a chronic stress situation in families which can generate distressing thoughts about paying household expenses, and leads to feelings of fear, anxiety and uncertainty regarding one’s ability to maintain the current standard of living [7, 35].…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%